Mechanistic Population Pharmacokinetic Model of Oseltamivir and Oseltamivir Carboxylate Accounting for Physiological Changes to Predict Exposures in Neonates and Infants. Issue 1 (26th February 2020) - Gibiansky, Leonid; Ravva, Patanjali; Parrott, Neil J.; Bhardwaj, Rajinder; Zwanziger, Elke; Grimsey, Paul; Clinch, Barry; Sturm, Stefan
Abstract : A mechanistic population‐pharmacokinetic model was developed to predict oseltamivir exposures in neonates and infants accounting for physiological changes during the first 2 years of life. The model included data from 13 studies, comprising 436 subjects with normal renal function (317 pediatric subjects (≥ 38 weeks postmenstrual age (PMA), ≥ 13 days old) and 119 adult subjects < 40 years). Concentration–time profiles of oseltamivir and its active metabolite, oseltamivir carboxylate (OC), were characterized by a four‐compartment model, with absorption described by three additional compartments. Renal maturational changes were implemented by description of OC clearance with allometric function of weight and Hill function of PMA. Clearance of OC increased with weight up to 43 kg (allometric coefficient 0.75). Half the adult OC clearance was reached at a PMA of 45.6 weeks (95% confidence interval (CI) 41.6–49.6) with a Hill coefficient of 2.35 (95% CI 1.67–3.04). The model supports the European Union/United States‐approved 3 mg/kg twice‐daily oseltamivir dose for infants < 1 year (PMA ≥ 38 weeks) and allows prediction of exposures in preterm neonates.